Homalopetalum joinvillense (Epidendreae; Epidendroideae; Orchidaceae): a new species from Southern Brazil - Mancinelli, Werner Siebje; de Camargo Smidt, Eric (Phytotaxa, 2015)
Homalopetalum joinvillense (Orchidaceae) is a new species found in Joinville (Brazil). This species presents morphological similarity with Homalopetalum alticolum, but it differs from that and another species of this genus by a combination of an oblong-obovate lip with a slightly denticulate lip margin, a callus divided in two parts, globose in the internal part and conical in the external part, and an erose clinandrium. This article presents the complete description and the illustration of the new species, as well as an identification key for the genus.